Easy peak tracking in CE‐UV and CE‐UV‐ESI‐MS by incorporating temperature‐correlated mobility scaling. Issue 12 (23rd May 2013) - Li, Bin; Petersen, Nickolaj J.; Andersen, Line H.; Hansen, Steen H.; El, Ziad
<x xml:space="preserve">Abstract</x> A simple data reconstruction technique in CE‐UV‐ESI‐MS (where UV stands for ultraviolet) is presented to overcome the drift in mobilities caused by various factors compromising the reproducibility of such data, for example Joule heating effects and the variation in thermostatic control along the capillary, drift in EOF and the suction effect caused by the nebulizing gas in coaxial CE‐MS interfaces. We present here a method to transform the traditional time‐based electropherogram into the corresponding temperature‐correlated mobility scale allowing tracking of analytes independent from capillary dimensions, electric field strengths, temperature control, and distance between the detectors. The main principle of this alignment is based on including the current in the mobility calculations and relating this to the initial electrical resistance of the buffer‐filled capillary. The temperature‐correlated mobility calculation eliminates the peak shifts due to the viscosity changes, improves the precision of peak identification using the observed temperature‐correlated mobilities, and allows a direct comparison of signals from different detection combinations. The method allows peaks from normal CE‐UV separations to be correlated with the corresponding peak obtained by MS detection in CE‐MS even for differences in capillary dimensions and thermostatic control.